2011
DOI: 10.3390/s120100092
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Efficient Cooperative Hierarchical MIMO Clustering Scheme for Wireless Sensor Networks

Abstract: In this work, we present an energy efficient hierarchical cooperative clustering scheme for wireless sensor networks. Communication cost is a crucial factor in depleting the energy of sensor nodes. In the proposed scheme, nodes cooperate to form clusters at each level of network hierarchy ensuring maximal coverage and minimal energy expenditure with relatively uniform distribution of load within the network. Performance is enhanced by cooperative multiple-input multiple-output (MIMO) communication ensuring ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…if not unique then (8) randomly select a node from and compose a CG with ; (9) store this CG in the allocation table; (10) mark this node as traversal, and update ; (11) else if unique then (12) and compose a CG; (13) store this CG in the allocation table; (14) mark as traversal, and update ; (15) else if none then (16) end this cycle; (17) where is the given BER; and are the numbers of the sending node and the receiving node; 0 is the noise power density.…”
Section: Energy Consumption Of Dsc-mimomentioning
confidence: 99%
See 1 more Smart Citation
“…if not unique then (8) randomly select a node from and compose a CG with ; (9) store this CG in the allocation table; (10) mark this node as traversal, and update ; (11) else if unique then (12) and compose a CG; (13) store this CG in the allocation table; (14) mark as traversal, and update ; (15) else if none then (16) end this cycle; (17) where is the given BER; and are the numbers of the sending node and the receiving node; 0 is the noise power density.…”
Section: Energy Consumption Of Dsc-mimomentioning
confidence: 99%
“…The experimental results showed that CMIMO could significantly reduce energy consumption and extend the network lifetime. Nasim et al proposed an energy-efficient hierarchical cooperative clustering scheme for wireless sensor networks [8]. According to this protocol, nodes cooperated to form clusters at each level of network hierarchy ensuring maximal coverage and minimal energy expenditure with relatively uniform distribution of load within the network.…”
mentioning
confidence: 99%
“…(1) for all i∈H do /*i represents a source node; H represents all the source node without traversal*/ (2) mark i as traversal, and update H; (3) for all j ∈H do /*j represents a source node */ (4) calculate the distance d between i and j; (5) end for (6) select the node k whose d satisfies Condition 1 and Condition 2; /* Condition 1: d<d max ; Condition 2: max{d}。*/ (7) if k not unique then (8) randomly select a node from k and compose a CG with I; (9) store this CG in the allocation …”
Section: Energy Consumption Of Gcmimomentioning
confidence: 99%
“…The experimental results showed that CMIMO could significantly reduce energy consumption and longer the network lifetime. Nasim proposed an energy efficient hierarchical cooperative clustering scheme for wireless sensor networks [8]. According to this protocol, nodes cooperated to form clusters at each level of network hierarchy ensuring maximal coverage and minimal energy expenditure with relatively uniform distribution of load within the network.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual MIMO allows wireless sensor network to obtain an effect similar to MIMO communication, and reduces the energy consumption of the entire network. Currently, researchers have made a lot of good virtual MIMO communication scheme, such as CMIMO [2], HV-MIMO [3], CCP [4], MIMO-CCRN [5] and the like. These virtual MIMO communication scheme solve the problem of energy consumption in WSN communication, but they do not solve low energy efficiency situation in the large-scale high-density WSN.…”
Section: Introductionmentioning
confidence: 99%